(untitled) (Global Journal of Management and Business Research, 2011)
Global financial crisis threatens the genuine investors and institutional investors who have parked their funds in financial assets. The developing countries follow the models and financial products especially the structured products the developed countries introduce and trade in their countries’ capital markets. Malaysia also has introduced these financial products in Bursa Malaysia and allowed trading. In this article we try to trace the growth of these products both in Islamic and conventional segments of capital market. Our aim is to give an over view of the different kinds of structured products, their features and differences among them. We point out the inherent risks in these products and how it is difficult to quantify when they are not based on cash flows and reference portfolio of assets. We caution the regulatory bodies to be vigilant about exotic structured products such as synthetic CDOs and CDO2 which are highly unreliable and not based on any underlying and cash flows.